Use of viscosupplementation for the recovery of active football players complaining of knee pain - Migliore A; Giannini S; Bizzi E; Massafra U; Cassol M; Michael Abilius MJ; Boni G (Dove Medical Press, 2018)
Alberto Migliore,1 Silvana Giannini,2 Emanuele Bizzi,1 Umberto Massafra,1 Maurizio Cassol,3 Martin Jose Michael Abilius,1 Giovanni Boni4 1Operative Unit of Rheumatology, San Pietro Fatebenefratelli Hospital, Rome 00189, Italy; 2Department of Radiology, Villa Stuart Sport Clinic, Rome 00136, Italy; 3Department of Internal Medicine, San Pietro Fatebenefratelli Hospital, Rome 00189, Italy; 4ANTIAGE Sportive Medicine Ambulatory Department (Ambulatorio di Medicina dello Sport Antiage), Foligno, Italy Objective: The aim of this study is to investigate the effect of intra-articular hyaluronic acid administration in active football players complaining of knee pain after sports activity. Efficacy and safety profiles of intra-articular hyaluronic acid and time needed for football players to recover and restart sports activity were examined.Methods: Clinical data of active football players reporting knee pain after sports activity were included in this retrospective study. All patients who received an intra-articular injection at time 0 and after 2 weeks were included in the study. Patients underwent laboratory examination, knee X-ray, ultrasound, and clinical examination before receiving the intra-articular injection. Effusions or cysts were drained before injections. Lequesne index score, pain visual analog scale (VAS) score, and patient’s global assessment score were recorded at time 0 (day of the first injection), 1 and 2 days after the first injection, at 2 weeks (day of the second injection), and at follow-up visits. Only data from patients completing the follow-up were analyzed.Results: Data from 17 patients were analyzed: 16 males and one female, of which three were professional players (two males and one female) and 14 were nonprofessional players. The mean age of patients was 39.8±11.8 years. Two patients (one male and one female) showed joint effusion. Two patients reported relevant joint pain after injection that regressed without any medication. At the first week, all parameters examined indicated improvement that was maintained until the end of follow-up. One day after the first and second injection, patients reported a slight increase in pain VAS score, which was not statistically significant, and the pain resolved after 1 day. All patients successfully restarted playing after the first injection within 3.1±2.0 days and kept playing after the second injection following our indication (1 day of break).Conclusion: The use of a medium-molecular weight hyaluronic acid in football players affected by knee osteoarthritis seems efficacious and safe and resulted, in our experience, a stable improvement of symptoms; moreover, it allowed a rapid restart of sports activity. Larger studies on larger populations are needed to confirm these findings. Keywords: sports, hyaluronic acid, intra-articular, injection, football, trauma